Bronchial Dieulafoy: Diagnostic Utility of Endobronchial Ultrasound - Chee Kiang Phua; Chee Kiang Tay; Carrie Kah Lai Leong (Respirology Case Reports)
ABSTRACT We report a case of bronchial Dieulafoy presenting with haemoptysis, initially resembling an endobronchial tumour on bronchoscopy. This case highlights the critical role of EBUS in the assessment of suspicious endobronchial lesions and in preventing potentially life‐threatening complications from inadvertent biopsy.